Secrets of Prague - Černý, David (Grada, 2024)
Do you know why the bridge gate between the Lesser Town bridge towers does not face out on Charles Bridge but is at a slant? Do you know what is written in a message to future generations and which was hidden in the wooden statue of the apostle of Doubting Thomas on the Prague astronomical clock?
Keywords: Architektura; Průvodce